Murphy and Kate - Howard, Ellen; Graham, Mark, 1952- (New York : Simon & Schuster Books for Young Readers, 1995)
Kate and her dog Murphy are best friends, and when Murphy dies Kate does not think she can ever be happy again.
Keywords: Dogs -- Fiction; Death -- Fiction